PERJALANAN MAHASISWA INDONESIA PENERIMA BEASISWA DI ERA SOEKARNO : DARI HARAPAN INTERNASIONALISME KE DAMPAK KEBIJAKAN ANTI-KOMUNISME DI ERA SOEHARTO - Aryadi, Arsha Medina; Fernandha, Rizqy Dini (Jurnal Sosial Humaniora Sigli, 2024)
In the 1960s, Soekarno sent thousands of students under the Service Bond Student program (MAHID) to continue their education abroad in several communist countries, such as the Soviet Union with the hope that the students who were given scholarships could return and develop Indonesia after studying abroad. However, with the occurrence of the G30SPKI movement, this dream was eliminated by depriving them of their citizenship rights due to anti-communism policies. The research method used in writing this article is a normative legal research method by conducting a literature study to obtain secondary data. The data that has been compiled and obtained in such a way will later be processed with a qualitative descriptive analysis method, then the writing in this research will be carried out using the type of descriptive research nature. Therefore, the presence of 1965 Exiles also provides an expansion of academic studies in the social sciences regarding the views on what is called being Indonesian abroad.Keywords: Exile, Anti-Communism, 1945, G0SPKI